Industry 4.0 : the Industrial Internet of Things - Gilchrist, Alasdair (Berkeley, CA : Apress ; 2023, 2016)
Explore the current state of the production, processing, and manufacturing industries and discover what it will take to achieve re-industrialization of the former industrial powerhouses that can counterbalance the benefits of cheap labor providers dominating the industrial sector. This book explores the potential for the Internet of Things (IoT), Big Data, Cyber-Physical Systems (CPS), and Smart Factory technologies to replace the still largely mechanical, people-based systems of offshore locations. Industry 4.0: The Industrial Internet of Things covers Industry 4.0, a term that encapsulates trends and technologies that could rewrite the rules of manufacturing and production. What are the Industrial Internet and Industrial Internet of Things Which technologies must advance to enable Industry 4.0 What is happening today to make that happen What are examples of the implementation of Industry 4.0 How to apply some of these case studies What is the potential to take back the lead in manufacturing, and the potential fallout that could result.
1. Introduction to the Industrial Internet -- 2. Industrial Internet Use Cases -- 3. The Technical and Business Innovators of the Industrial Internet -- 4. IIoT Reference Architecture -- 5. Designing Industrial Internet Systems -- 6. Examining the Access Network Technology and Protocols -- 7. Examining the Middleware Transport Protocols -- 8. Middleware Software Patterns -- 9. Software Design Concepts -- 10. Middleware Industrial Internet of Things Platforms -- 11. IIoT WAN Technologies and Protocols -- 12. Securing the Industrial Internet -- 13. Introducing Industry 4.0 -- 14. Smart Factory -- 15. Getting from here to there - a roadmap.
Description based on publisher-supplied MARC data.
Keywords: Computer communication systems; Computer input-output equipment; Computers and civilization; Computer Communication Networks; Computers and Society; Hardware and Maker